2009
DOI: 10.1002/bjs.6636
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte depletion of perioperative blood transfusion does not affect long-term survival and recurrence in patients with gastrointestinal cancer

Abstract: Leucocyte depletion is not associated with better long-term survival and lower recurrence rates in patients with gastrointestinal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…However, recent animal studies have proposed that old red blood cells, rather than leukocyctes or soluble fractions, are responsible for the tumor‐promoting effects of both autologous and allogeneic blood transfusions . This was proven in demonstrating that neither allogeneic nor autologous blood treated with leukocyte‐depletion filtration affected cancer recurrence in patients undergoing oncological surgeries …”
Section: Discussionmentioning
confidence: 99%
“…However, recent animal studies have proposed that old red blood cells, rather than leukocyctes or soluble fractions, are responsible for the tumor‐promoting effects of both autologous and allogeneic blood transfusions . This was proven in demonstrating that neither allogeneic nor autologous blood treated with leukocyte‐depletion filtration affected cancer recurrence in patients undergoing oncological surgeries …”
Section: Discussionmentioning
confidence: 99%
“…The administration of peri‐operative blood transfusions (PBT) has been associated with prognosis in several organ‐specific cancers, including oesophageal, gastric, colorectal and hepatic carcinomas . It has been suggested that immunosuppressive mechanisms in the PBT recipient have an impact on cancer‐related outcomes owing to the large amounts of antigen in transfused blood products.…”
Section: Introductionmentioning
confidence: 99%
“…The nonsignificant and small RR of colorectal cancer recurrence secondary to nonleukoreduced ABT across the three RCTs dampened the enthusiasm for investigating this purported ABT effect by means of RCTs and also by means of observational studies. Between patients with gastric cancer randomly assigned to receive nonleukoreduced versus leukoreduced ABT, there was no difference in survival or cancer recurrence . Observational studies continued to generate debate by sometimes reporting significant associations of nonleukoreduced ABT with cancer recurrence, cancer‐specific mortality, and/or all‐cause mortality, until two recent meta‐analyses of ABT and adverse clinical outcomes in colorectal cancer and hepatocellular cancer resurrected the controversy about a purported adverse ABT effect.…”
mentioning
confidence: 99%